Effects of solar radiation and night temperature on potential maize yield in two different crop years - Bódi, Zoltán; Nagy, János (Precision Crop Production, 2025)
Hungary's climate is undergoing change, and the heat unit (GDD) values have increased annually in the past nearly 50 years. In this study, we evaluate the performance of a maize hybrid in normal (2021) and drought (2022) crop years, along with the optimal agrotechnical factors (drip irrigation and high nutrient). In the potential experiment, we obtained a yield of 20.65t/ha in 2021 and 13.8t/ha in 2022. We examined the reasons for the large (33%) yield difference between the two years. By breaking down the weather data daily, it can be determined that the solar radiation (SR) and sunshine duration during the V6-V8 stage have an effect, and cloud cover affects the development of the reproductive organs of maize (ear differentiation). In the two years studied, we measured a significant difference in the SR value in the V6-V12 development stages (36% and 30% less SR was measured in 2022 vs 2021). The higher temperature (R1-R6) (2022) accelerated the phenological development of maize, so maize reached the black layer formation faster. The results indicate that in the future, we must also address the responses of maize to temperature changes with different levels of solar radiation and their dry matter incorporation dynamics.